PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP JOB PERFORMANCE MELALUI WORK ENGAGEMENT SEBAGAI VARIABEL INTERVENING PADA KARYAWAN PLAZA TOYOTA GREEN GARDEN - Maharani Ade Sapitri (2022)
This study aims to determine whether there is an influence between transformational leadership on job performance through work engagement as an intervening variable for Plaza Toyota Green Garden employees. This research is a quantitative research with a sample of 42 employees of the Showroom Plaza Toyota Green Garden with a sampling technique using saturated sampling technique. The analysis technique uses the path analysis method with the help of SmartPLS 3.0. Hypothesis testing obtains that transformational leadership has a positive and significant effect on the job performance of Plaza Toyota Green Garden employees, transformational leadership has a positive and significant effect on work engagement of Plaza Toyota Green Garden employees, work engagement has a positive and significant effect on job performance of Plaza Toyota Green Garden employees, and transformational leadership has a positive and significant effect on job performance through work engagement as an intervening variable for Plaza Toyota Green Garden employees.